Expression of Man’s Portrait in the Dictionary of the Southern South Aukštaitian Subdialects - Ragaišienė, Vilija (Vilnius University Open Series, 2020)
The article examines the expression of a person living in the area of the Southern South Aukštaitian, describing the appearance and physical characteristics, features of the character and temper, social status and relationships based on the material in the two-volume Comprehensive Dictionary of the Southern South Aukštaitian Subdialects (Vol I published in 2016, Vol II in 2019). To begin with, the study includes all sentences that use the word man. It is also based on the examples where it is replaced by pronouns (I, you, he, she etc.), kinship terms (mother, father, brother, sister, grandson, granddaughter, aunt, uncle etc.), nouns that designate individuals by the gender (boy, girl, woman, woman, man etc.) and other. All the sentences in the dictionary that speak of man are analysed. The lexicographic data show that a person (man, woman, child) is an individual living in the Southern South Aukštaitian area. He/she is a kind-hearted, sincere, open, tolerant, cheerful and witty, hardworking and creative representative of the people and dialect; also energetic and persevering, though not always physically strong and capable. The analysis carried out reveals the genesis of the concept of man, and shows the attitude of several generations to man. The illustrative sentences highlight the stereotypical image of a person living in the Southern South Aukštaitian area (cheerful, generous, and hardworking, believes in God and is superstitious, values the family etc.) and show the new emerging traits (laziness, drinking, stealing, disobeying, immoral and dishonest etc.). The analysis of the dialectical discourse reveals the difference between the archaic and contemporary approaches; the ongoing changes in material and spiritual life are revealed. The material in the dictionary reveals the wonderful harmony of man and nature, which has been formed over several centuries, with the community living in a relatively isolated, closed environment. The worldview of man living in the area of the Southern South Aukštaitian area is interwoven with the old mythological world, the mysteries of the Catholic faith, and the realities of the present. Although the world is changing, old values and customs are disappearing and villages are abandoned, people are optimistic about the world. Work, family, faith in God and man are their greatest values.